Implementing Games Based Teaching Strategy in Teaching Speaking - Sokhira Linda Vinde Rambe (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study investigated types of games applied by the teachers in teaching speaking, described the problems faced by the teachers in implementing the games, and found out the solutions done to overcome the problems. Then, this study was in a form of qualitative research applying descriptive method in analyzing the data. Observation and interview were conducted to collect the data related to the implementation of the games, and descriptive data analysis was used in analyzing them. This study found that there were some games used by the teachers in teaching speaking e.g find someone who, hot seat, whispering, interview, survey, finger up and down, memory chain, and fact or fake game. The problems also happened during speaking practice like the use of mother tongue due to lack of vocabulary, cheating, and passive students. Finally, the teachers did solutions to solve the problems like giving clear instructions, and setting the rules before playing the games.